The relationship between ESG and corruption on potential risks: An analysis of Asian bank from 2017 to 2022 - Annisa Nurbaiti; Ali Riza Fahlevi; Muhammad Rayhan Arifanka (Global Business & Finance Review (GBFR), 2024)
Purpose: In this research, we aim to determine the relationship between environmental, social, and governance (ESG) and corruption on potential risks with banking samples from Asian countries in 2017-2022. Design/methodology/approach: This study uses a sample of 451 Asian public banking companies listed on each stock exchange in 23 countries from 2017 to 2022. Then, in this study, we use panel data, with accounting and financial data obtained from Thomson Reuters, while country characteristics such as GDP, and corruption are ob-tained from CPI and World bank Database. Findings: We find evidence that ESG can increase the occurrence of banking risk. Furthermore, we find that a high level of corruption will increase banking risk. The results of this study are robust to using alternative measures of potential risk. Research limitations/implications: This study has several limitations, including that it does not specifically consider the cultural characteristics of each country, using a sample of 451 banks in 23 countries. Originality/value: Using the banking sector in Asia, this study successfully clarifies the role of ESG as well as the moderating role of corruption on Potential Risk.
Keywords: 650; ESG; Corruption; Banking Risk